Analisis Profitabilitas dan Leverage Terhadap Agresivitas Pajak : PengungkapanCSR sebagai Variabel moderasi - Ida Candra Dewi (Yayasan Literasi Ilmiah Indonesia, 2022)
The study aims to test the effect of profitability and leverage on tax aggressiveness with CSR disclosure as a moderation variable. This study used samples obtained from manufacturing companies listed on the Indonesia Stock Exchange in 2016-2020, using the purposive sampling method with a sample number of 39 companies with 147 annual financial statements. The method used in this study is multiple linear regression analysis to prove the effect of profitability and leverage on tax aggressiveness. Moderate Regression Analysis (MRA) test to prove the effect of CSR disclosure in moderating profitability and laverage on tax aggressiveness. The results of this study show that profitability has a positive effect on tax aggressiveness. Leverage has no effect on tax aggressiveness. CSR disclosure cannot moderate the positive relationship of profitability to tax aggressiveness. CSR disclosure cannot moderate the influence of leverage on tax aggressiveness. This research is an update of the research conducted by Sidik & Suhono, (2020) by adding CSR disclosure variables as moderation variables.